Channeling Sabina - Eriksen, Telaina Morse (Ars Medica, 2014)
He follows a path inside you, decorated since infancy, carefully guarded, whispering to God in apple tones. And then, like Carl Jung, he pauses to excavate what he considers treasure. And after awhile he doesn't even have to ask anymore, you just give.